MODIFYING OF SECONDARY ALLOYS - V. Yu. Stetsenko (Литьë и металлургия)
It is shown that impurity modifying of secondary alloys inefficiently because of the high contents in fusion of high-disperse nonmetallic particles. They promote receiving not modified microstructure and pollution of castings by nonmetallic inclusions. Effective ways of modifying of secondary alloys are the methods of the accelerated hardening of castings and hereditary modifying